1995
DOI: 10.2337/diab.44.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Counterregulation of Hypoglycemia: Skeletal Muscle Glycogen Metabolism During Three Hours of Physiological Hyperinsulinemia in Humans

Abstract: We examined the role of skeletal muscle in counterregulation of hypoglycemia (3.4 +/- 0.1 mmol/l) in 12 nondiabetic individuals (age 26 +/- 1 years, body mass index 24.2 +/- 0.7 kg/m2) during physiological hyperinsulinemia (280 +/- 25 pmol/l) compared with euglycemia (4.8 +/- 0.1 mmol/l). During hypoglycemia, hepatic glucose output (3-[3H]-glucose) was greater (7.72 +/- 2.72 mumol.kg-1.min-1, P < 0.01), glucose uptake was approximately 49% lower (21.20 +/- 3.55 mumol.kg-1.min-1, P < 0.005), and glucose clearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…This apparent discrepancy between both our results is probably explained by the presence of higher insulin levels in the study by Shamoon et al [56] and also it cannot be excluded that some suppression of glycogen synthase activity would have been unmasked if a constant euglycaemic control situation had been present. Our results are in agreement with those of a very recent study by Cohen et al [20], demonstrating decreased glycogen synthesis in skeletal muscle during mild hypoglycaemia and physiological hyperinsulinaemia in healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This apparent discrepancy between both our results is probably explained by the presence of higher insulin levels in the study by Shamoon et al [56] and also it cannot be excluded that some suppression of glycogen synthase activity would have been unmasked if a constant euglycaemic control situation had been present. Our results are in agreement with those of a very recent study by Cohen et al [20], demonstrating decreased glycogen synthesis in skeletal muscle during mild hypoglycaemia and physiological hyperinsulinaemia in healthy subjects.…”
Section: Discussionsupporting
confidence: 83%
“…In recent studies we and others -= have demonstrated that muscle glucose uptake is dra-_~ 5-matically reduced during hypoglycaemia in healthy man [18][19][20]. However, the specific cellular events in-~ 4-volved in this phenomenon require further examination.…”
mentioning
confidence: 99%
“…Indeed, the restraint on glucose disposal was found to be entirely due to a decrease in glycogen synthesis (44), primarily in nonoxidative skeletal muscle (45). Results from such studies are complicated by the fact that large doses of insulin are used to induce hypoglycemia in vivo, and that systemic hypoglycemia inevitably invokes a surge of counterregulatory hormones, especially catecholamines, which are known to impair muscle glucose uptake and glycogen synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have reported a marked decrease in muscle glucose disposal during insulin-induced hypoglycemia in humans relative to euglycemia (44)(45)(46). Indeed, the restraint on glucose disposal was found to be entirely due to a decrease in glycogen synthesis (44), primarily in nonoxidative skeletal muscle (45).…”
Section: Discussionmentioning
confidence: 97%
“…Because the arterial plasma glucagon level and glucagon secretion decreased so little (if at all) in response to hyperglycemia, it is evident that hyperglycemia per se, even in the presence of modestly increased plasma insulin, had little effect on basal glucagon secretion. On the other hand, a decrease in plasma glucose from 5.8 to 5.2 mmol/l triggered a significant increase in arterial glucagon and glucagon secretion (>200% of basal) at a plasma glucose value well above the well-recognized threshold of 3.8 mmol/l observed in the presence of insulin-induced hypoglycemia in humans (1,12,25,32,33) and dogs (2)(3)(4)15). However, because basal plasma glucose levels in overnight-fasted humans (~4.7 mmol/l) (1-6) are usually lower than those in overnightfasted dogs (~5.8 mmol/l), the extent of the decrease in plasma glucose required to initiate an increase in glucagon secretion in the present study (0.6 mmol/l) was only about half (~1.2 mmol/l) of that reported to initiate glucagon release in response to insulin-induced hypoglycemia in humans (1,25).…”
Section: Discussionmentioning
confidence: 99%